Effect of operational parameters on photodegradation of Direct Blue 53 by silver loaded-titania under ultraviolet and solar illumination. (August 2015) - Sobana, N.; Subash, B.; Swaminathan, M.
Abstract: Photocatalytic degradation of Direct Blue 53 (DB 53) by Ag loaded TiO2 has been investigated under UV and solar light. Photodeposition of 2.0% Ag on the surface of TiO2 enhanced its photoactivity in DB 53 degradation. Optimal experimental conditions on catalyst amount, pH and dye concentration have been investigated. Addition of some inorganic oxidizing species such as H2 O2, (NH4 )S2 O8 and KBrO3 up to a certain concentration enhanced the rate of degradation. The increased photoactivity of Ag–TiO2 than bare TiO2 under UV and solar light illumination can be ascribed to the effect of silver deposits acting as electron traps on Ag–TiO2 surface. The degradation efficiency of Ag–TiO2 under solar radiation is higher than its efficiency in UV light.